Expression of inflammatory cytokines in CADASIL and their associations with clinical and neuroimaging features - Bai, Li; Yan, Haotian; Wang, Zhongao; Peng, Qing; Jin, Haiqiang; Sun, Yunchuang; Li, Fan; Zhang, Wei; Zhang, Zihao; Wang, Zhaoxia; Yuan, Yun; Hao, Hongjun; et al. (Frontiers in Immunology, 2025)
ObjectivesThe aim of our study is to explore the expression levels of inflammatory cytokines in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), and to assess the correlation between inflammatory cytokines and clinical/magnetic resonance imaging (MRI) features of the patients.MethodsWe recruited 54 patients with CADASIL and 28 healthy controls and detected the expression levels of the following inflammatory cytokines in peripheral blood: interferon (IFN)-γ, tumor necrosis factor (TNF)-α, TNF-β, interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-17F, and IL-22. We also analyzed the relationship between the expression levels of the inflammatory cytokines and the clinical/MRI features.ResultsThe expression of most inflammatory cytokines were significantly higher in CADASIL patients than in healthy controls, including IFN-γ (z = −5.335, P < 0.001), TNF-α (z = −4.880, P < 0.001), TNF-β (z = −2.401, P = 0.019), IL-1β (z = -2.831, P = 0.007), IL-4 (z = −4.039, P < 0.001), IL-5 (z = −4.523, P < 0.001), IL-6 (z = −3.545, P < 0.001), IL-8 (z = −5.667, P < 0.001), IL-17F (z = −3.986, P < 0.001) and IL-22 (z = −5.325, P < 0.001). The increased expression level of TNF-β was correlated with abnormal mRS scores in patients with CADASIL (odds ratio [OR] = 6.147, 95% CI: 1.324-28.535; P = 0.020) after adjustment for age, sex, history of hypertension and history of diabetes. The expression level of TNF-β was also associated with MMSE (β = -0.281, 95% CI:-5.325–0.866, P = 0.008) and apathy scores (β = 0.388, 95% CI:2.554-16.328, P = 0.008) after adjusting for age, sex, educational years, history of hypertension and history of diabetes. There was also a positive correlation between the expression level of TNF-β and the number of CMBs in deep (β = 0.314, 95% CI:2.989-39.461, P = 0.023) and lobar region (β = 0.433, 95% CI:15.363-59.857, P = 0.001) after adjusting for age, sex, history of hypertension and history of diabetes.ConclusionsOur results indicate that diffuse inflammatory pathway activation occurs in CADASIL. The increased expression level of TNF-β was associated with higher CMBs burden and poor clinical scores. Our findings suggest that the inflammatory pathway, particularly the TNF-related inflammatory pathway, may be involved in the disease progression of CADASIL.